• Asignatura: Matemáticas
  • Autor: keylitis20pcuv3t
  • hace 9 años

simplificacion de 4a- {3b-(a-b)-(3a-b)-2b+3a}

Respuestas

Respuesta dada por: cristhianzg
12

4a - { 3b - (a - b) - (3a - b) - 2b + 3a } ==> Se aplicó ley de signos.

4a - { 3b - a + b - 3a +b - 2b + 3a } ==> 3b + b + b - 2b = 3b ( se sumo las "b" )

4a - { 3b - a - 3a + 3a } ==> - a - 3a + 3a = - a ( se sumo las "a" )

4a - { 3b - a } ==> Se aplicó ley de signos

4a - 3b + a ==> Se sumaron las "a"

5a - 3b

Rpta: 5a - 3b

Saludos...

Preguntas similares